Stakeholder Salience Analysis in the Policy Formulation of Anti-Violence Against Women and Children - Putri Marzaniar; Agustinus Subarsono (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, Indonesia, 2023)
This article explores stakeholders influence in the policy formulation of anti-violence against women and children by using the stakeholder salience model as a conceptual framework. Stakeholder engagement in policy formulation is essential to achieving optimal policy practise and performance. However, the contestation of interests and imbalance of power between stakeholders in the policy formulation of anti-violence against women and children inhibit the development of policy alternatives based on problem solving, resulting in low policy performance. The research method used is qualitative research with a case study approach, and the stakeholder analysis method is applied to the data analysis. The research findings demonstrate that the policy formulation of anti-violence against women and children is dominated by dependent stakeholders with only power and legitimacy attributes, while the attributes of urgency are not available, reflected in their inattentiveness in providing a quick response to the rising cases of violence and their lack of knowledge on the issue of violence. This study concludes that stakeholders' influence in the policy process is limited. Stakeholders are only involved during public hearings, and the policy is only drafted and discussed by the policy elite, specifically Commission VI of the Aceh Legislative Council, an expert’s team, and the Aceh Women's Empowerment and Child Protection Unit. It indicates that stakeholder engagement is only to gain legitimacy for policy decisions. This research contributes to providing knowledge about stakeholder dynamics in policy formulation contexts and theoretical knowledge about the creation of the most powerful and influential stakeholders for maximising policy formulation and policy performance.